The Power Of Self-Acceptance - Sotiriou, Lydia; Nakhleh, Floriana; Papanastasiou, Fyllia (Open Schools Journal for Open Science, 2025)
In our fast-paced world focused on success and productivity, self-criticism becomes common as we feel compelled to change who we are to fit in. But what if true contentment lies in embracing who we already are? Self-acceptance involves embracing both strengths and personal faults without judgment. It leads to improved mental health, better relationships, and personal growth. Strategies for self-acceptance include setting healthy boundaries, avoiding self-blame, and focusing on positivity. Self-acceptance fosters resilience, better decision-making, and enhanced collaboration in various aspects of life, including school, work, and sports.